Spectroscopic data of Rb-isoelectronic Zr and Nb ions for astrophysical applications. Issue 3 (17th August 2021) - , Jyoti; Kaur, andeep; Arora, Bindiya; Sahoo, B K
ABSTRACT: We present high-accuracy spectroscopy data of line strengths, transition probabilities, and oscillator strengths for the allowed transitions among the nS 1/2, nP 1/2, 3/2, and n ′ D 3/2, 5/2 states with n = 5 to 10 and n ′ = 4 to 10 of the Rb-isoelectronic Zr (Zr iv ) and Nb (Nb v ) ions. They can serve to analyse various astrophysical phenomena undergoing inside the heavenly bodies containing Zr and Nb elements. Since there is a lack of precise observational and calculated data for the spectroscopic properties in the above ions, their accurate determinations are of immense interest. The literature data, which are available only for a few selected low-lying transitions, have large discrepancies and they cannot be used reliably for the above purpose. After accounting for electron interactions through random phase approximation, Brückner orbitals, structural radiations, and normalizations of wave functions in the relativistic many-body methods, we have evaluated the electric dipole amplitudes precisely. Combining these values with the observed wavelengths, the above transition properties and lifetimes of a number of excited states of the Zr iv and Nb v ions are determined and compared with the literature data.